Understanding the societal impact of the social sciences and humanities: Remarks on roles, challenges, and expectations - Benedikt Fecher; Freia Kuper; Nataliia Sokolovska; Alex Fenton; Stefan Hornbostel; Gert G. Wagner (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2021)
This study investigates the contagious nature of tax avoidance by examining how narratives affect tax avoiding behavior. We adapt the idea of narrative economics indicating that individuals' actions are stimulated by stories that spread within a society. We employ two types of infection models to theoretically investigate how tax avoidance schemes spread over time and vanish eventually consistent with patterns known from epidemiology. We find that general tax avoidance can persist even if its expected outcome is negative, while specific tax avoidance schemes might vanish even though their expected outcome is positive. We find empirical support for the predicted dissemination of narratives related to both general and specific tax avoidance schemes in google n-grams. Finally, we show that dissemination of specific tax avoidance schemes is attenuated by anti-narratives in (social) media. Our findings help to understand how tax avoidance spreads, under what conditions anti-avoidance measures can effectively curb tax avoidance and point towards the crucial role of transparency of enhanced enforcement by visible narratives.Science is increasingly expected to help in solving complex societal problems in collaboration with societal stakeholders. However, it is often unclear under what conditions this can happen, i.e., what kind of challenges occur when science interacts with society and what kind of quality expectations prevail. This is particularly pertinent for Social Sciences and Humanities (SSH), which are part of the object they study and whose knowledge is always subject to provisionality. Here we discuss how SSH researchers can contribute to adressing societal problems, what challenges might occur when they interact with societal stakeholders, and what quality expectations arise in these arrangements. We base our argumentation on the results of an online consultation among 125 experts in Germany (representatives from SSH, learned societies, stakeholders from different societal groups, and relevant intermediaries).
Keywords: 330; Social Sciences and Humanities; Societal Impact; Quality Criteria; Evaluation